2015
DOI: 10.14254/2071-8330.2015/8-1/6
|View full text |Cite
|
Sign up to set email alerts
|

Empirical study of the comfort of living and working environment – Ukraine and Europe: comparative assessment

Abstract: Abstract. is paper reports ndings from a comparative assessment of the "comfort" and "well-being" concepts which are used in socio-economic research to evaluate the living and working environment of the population. e use of indicators of material, social, and psychological needs satisfaction has become important as useful methodologies for the characterisation, evaluation and diagnostic of comfort. e assessment is based on the available statistical data of Ukraine and some European countries. e authors found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 3 publications
0
31
0
Order By: Relevance
“…As for Ukraine, the emigration in which is the subject of the study in this article, we revealed the corresponding reasons as well as their interrelation with socioeconomic basis of migration decisions in our preceding papers (Bilan, 2017;Mishchuk & Grishnova, 2015;Mishchuk et al 2018) and some other researches (Cohen, 2017;D'Silva & Samah, 2018;Holovatyi, 2014;Máté et al, 2018). At the same time, Ukrainian scientists, like their European counterparts who are studying the problem of brain gain in favour of more developed countries, for instance (Grenčíková et al 2017), are trying to find a common solution for all source countries in order to transform the process of intellectual migratory losses into the brain circulation and justify the policy measures that can enforce the benefits of circulation of knowledge and skills (Bilan & Bilan, 2011;Puraite et al, 2017;Sadova, 2010;Semiv & Hvozdovych, 2012;Stakanov, 2018).…”
Section: Literature Reviewmentioning
confidence: 76%
“…As for Ukraine, the emigration in which is the subject of the study in this article, we revealed the corresponding reasons as well as their interrelation with socioeconomic basis of migration decisions in our preceding papers (Bilan, 2017;Mishchuk & Grishnova, 2015;Mishchuk et al 2018) and some other researches (Cohen, 2017;D'Silva & Samah, 2018;Holovatyi, 2014;Máté et al, 2018). At the same time, Ukrainian scientists, like their European counterparts who are studying the problem of brain gain in favour of more developed countries, for instance (Grenčíková et al 2017), are trying to find a common solution for all source countries in order to transform the process of intellectual migratory losses into the brain circulation and justify the policy measures that can enforce the benefits of circulation of knowledge and skills (Bilan & Bilan, 2011;Puraite et al, 2017;Sadova, 2010;Semiv & Hvozdovych, 2012;Stakanov, 2018).…”
Section: Literature Reviewmentioning
confidence: 76%
“…Significant economic indicators, such as economic growth, migration and unemployment rate, or company competitiveness, are dependent, to a marked extent, upon the outcomes of research and development. In connection with competitiveness and research potential, it is also necessary to take into account factors that influence the assessment of their sustainability (Drastichová, 2015;Mishchuk & Grishnova, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Comfort, well-being, and quality of life concepts are considered powerful objectives in different contexts such as justice, economy, or the environment (Fracolli et al, 2011), as well urban planning and design. The adoption of indicators of material, social, and psychological needs satisfaction has become a significant tool in assessing quality of life and identifying and evaluating comfort and well-being characteristics (Mishchuk & Grishnova, 2015). Quality of life is considered a critical aspect in sustaining any urban environment (Serag El-Din et al, 2012), and the planner's aim is to upgrade comfort and well-being in every setting and for all inhabitants (Lotfi & Solaimani, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers concluded that material living standards, housing, and basic services; social connectivity; and personal health care are the major contributing factors in improving life quality. Mishchuk and Grishnova (2015) conducted a comparative assessment of comfort and well-being in Ukraine and some European countries. The researchers found that health care needs and conditions for life extension and protection of human rights were the most significant external migration factors.…”
Section: Introductionmentioning
confidence: 99%